Research on the Influence of Rotating Pair Clearance on the Dynamic Performance of the Main Mechanism of Gear Shaping Machine - Yayin He; Zhihong Liang (Jixie chuandong)
In order to study the influence of the rotating pair clearance on the dynamic performance of the main mechanism of gear shaping machine， the non-linear contact impact force model of the clearance with friction and the virtual prototype model of the main mechanism of gear shaping machine with the clearance rotating pair are established. By using the by mechanical dynamics analysis technology，the influence of the impact model parameters，clearance value and clearance number on the dynamic performance of the mechanism are studied. The results show that the root mean square of the slider speed error tends to be stable with the increase of the clearance， and there is a suitable clearance range， so that the root mean square value of the slider speed with multiple clearances is smaller than that with one clearance. The results of the study provide reference for selecting the material of the rotation pair clearance，and controlling the value and quantity of the motion pair clearance.